Perception of Consumer Towards Halal Labelled Cosmetic Products Among Muslimah Banten - Iswatun Hasanah; Purnama Rika Perdana; Iffan Ahmad Guffron; Syukron Arjuna; muawanah muawanah (Saintifika Islamica, 2022)
This study aimed to determine the influence of attitudes, subjective norms and perception control modified with religiosity, product knowledge of buying intentions and consumer behaviour in purchasing halal cosmetic products. The halal-labeled cosmetic sector is expected to thrive in Banten. The consumption and expenditure among Banten Muslimah on cosmetic products in personal body care, beauty and wellness products are increasing rapidly over time. At the same time, government bodies have to make sure that manufacturers comply with Banten Halal and Shari’a standards. The subject in this study is Muslimah students aged 17-23 years studying at UIN Sultan Maulana Hasanuddin Banten. This research uses purposive sampling in collecting the sample. The analytical method used is multiple linear regressions. A closed questionnaire is used in this research for up to 107 samples. This paper studies the effect of knowledge, attitude and practice on the perception of consumer toward halal labeled cosmetic products in Banten. This study is useful to fill the gaps in the Banten literature regarding the importance of knowledge and its relationship with the attitude and practice. The findings of this study show that religiosity, product knowledge, attitudes, subjective norms, and perception control have a positive and significant influence on consumer intentions in buying halal cosmetic products. All of that affects consumers' attitudes in choosing cosmetic products labeled halal. The marketing of halal products is no less competitive with non-halal cosmetic products. It is expected to know the halal label and its content for every cosmetic product that will be used to avoid products that are not halal or forbidden by Shari'a. It aims to care for and protect an Islamic worldview and life.